Predicting 90-day mortality at admission and 7 days post-admission among patients with hepatitis B virus-related acute-on-chronic liver failure - Fang Chen; Yuzhi Shi; Shurong Ran; Xueqin Liu; Jian Xu (Journal of the Pakistan Medical Association, 2020)
Predicting 90-day mortality at admission and 7 days post-admission among patients with hepatitis B virus-related acute-on-chronic liver failure